Rituximab maintenance therapy of follicular lymphoma in clinical practice. (15th May 2018) - Dührsen, Ulrich; Broszeit‐Luft, Stefanie; Dieing, Annette; Lück, Andreas; Porowski, Piotr; Reiser, Marcel; Schwinger, Ulrike; Klawitter, Sandra; Krumm, Katja; Jentsch‐Ullrich, Kathleen
Abstract: Standard of care for patients with symptomatic, advanced‐stage follicular lymphoma (FL) is rituximab‐containing chemoimmunotherapy followed by rituximab maintenance. This prospective, multicenter, noninterventional study analyzed how efficacy and safety data from randomized controlled trials translate into clinical practice in Germany. Both treatment‐naïve and relapsed/refractory patients with FL, who responded to rituximab‐containing induction and were scheduled for rituximab maintenance, were observed for 24 months. Effectiveness was measured by response and Kaplan‐Meier survival analysis. In addition, treatment patterns of induction and maintenance, as well as adverse events, were documented. The evaluable study population consisted of 310 first‐line patients and 173 relapsed/refractory patients, including 116 patients with initial Ann‐Arbor stage I/II and 20 patients with FL grade 3B. Regarding first‐line induction, a shift from R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) to R‐bendamustine was observed over time, as well as a decline in radiotherapy. 2‐year progression‐free survival rates were 88.3% (95% confidence interval [CI] 84.0‐92.6) for first‐line patients and 76.0% (95% CI: 68.8‐83.3) for relapsed/refractory patients. Conversion from partial to complete remission (PR, CR) occurred in 53.4% of analyzed first‐line patients with PR, resulting in 69.4% CRs at study end (relapsed/refractory: conversion in 42.9%, final CRs 57.9%). Safety results were consistent with the known safety profile of rituximab in this setting. Both treatment‐naïve and relapsed/refractory patients with FL show favorable 2‐year PFS rates and improvements in the remission status with postinduction rituximab monotherapy as maintenance and consolidation therapy. Abstract : This noninterventional study indicates that both treatment‐naïve and relapsed/refractory patients with follicular lymphoma benefit from rituximab maintenance following rituximab‐containing induction in clinical routine. Effectiveness and safety results were in line with data from randomized controlled trials, and tumor remission rates indicated both maintenance and consolidation of remission.